(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study looks at how Indian banks handle credit score risk under Basel III guidelines, with a strong emphasis on counterparty credit risk (CCR). Basel III seeks to enhance banks' flexibility during times of economic strain by enhancing capitalization, refining risk insurance, and implementing new policies such as the impact rate, enhanced administrative review (Pillar 2), and public exposures (Pillar 3). The observation examines how those reforms are implemented in Indian banks and evaluates how well they work to appease CCR. The results suggest that while significant progress has been made, more work needs to be done to properly comprehend the benefits of these reforms. Policymakers and banking institutions receive recommendations on how to improve credit risk management. This article analyses the application and efficacy of Basel III norms to control credit risk in Indian banks. It provides analysis and suggestions for improving risk management procedures to guarantee monetary stability.